Selective Nerve Root Transection in the Rat Produces Permanent, Partial Nerve Injury Models with Variable Levels of Functional Deficit. Issue 1 (January 2017) - Poppler, Louis H.; Schellhardt, Lauren M.; Hunter, Daniel A.; Yan, Ying; Mackinnon, Susan E.; Wood, Matthew D.; Moore, Amy M.
Abstract : Background: The goal of this study was to develop a partial, nonregenerative nerve injury model in a rat that results in permanently reduced motoneuron numbers and function. This model could serve as a platform for the study of therapeutics, such as a reverse end-to-side nerve transfer (i.e., supercharge). The authors hypothesized that transection of one or more of the L4 to L6 nerve roots supplying the sciatic nerve would cause a permanent reduction in muscle force. Methods: Rats were randomized into five groups that underwent variations of nerve root transections or sham injury. The L4 to L6 nerve roots were selectively transected and capped to prevent regeneration. Tibial and common peroneal nerves were harvested for quantitative histology and retrograde-labeled to assess the number of motoneurons projecting axons. Muscle force and relative muscle mass were assessed as metrics of postinjury motor function. Results: At 6 months, the number of motoneurons projecting axons and myelinated axon counts were reduced in both the tibial and common peroneal nerves after injury in all groups. Transecting both L4 and L5 or both L4 and L6 reduced motoneuron numbers sufficiently below sham numbers to reduce muscle force and mass in major muscles of the hindlimb innervated by both nerves. Transecting L4 reduced muscle force and mass in common peroneal–innervated muscles, whereas transecting L5 reduced muscle force and mass in tibial-innervated muscles. These findings were stable over time. Conclusion: Transection of nerve roots produces stable (time-independent) partial nerve injury models with a selective decrease in motor function.